(untitled) (Scientific journal of the Fergana State University, 2024)
Transboundary protected areas play a unique role in preserving biological and landscape diversity and creating ecological networks on our planet. The article analyzes the theoretical basis for the creation of transboundary protected natural areas as one of the important conditions for the conservation of biological and landscape diversity and their effective use for various purposes. Also, international organizations have also considered the idea of ​​managing transboundary resources, especially as protected natural areas.